Molecular Characterization of African Swine Fever Virus, China, 2018 - Ge, Shengqiang; Li, Jinming; Fan, Xiaoxu; Liu, Fuxiao; Li, Lin; Wang, Qinghua; Ren, Weijie; Bao, Jingyue; Liu, Chunju; Wang, Hua; Liu, Yutian; Zhang, Yongqiang; et al. (Emerging infectious diseases, 2018)
On August 3, 2018, an outbreak of African swine fever in pigs was reported in China. We subjected a virus from an African swine fever-positive pig sample to phylogenetic analysis. This analysis showed that the causative strain belonged to the p72 genotype II and CD2v serogroup 8.